STUDI KASUS KETERAMPILAN DASAR AKADEMIK ANAK USIA 4 TAHUN DI TAMAN KANAK-KANAK - Santi Kusuma Dewi (P3M STKIP 'Aisyiyah Riau, 2016)
This research was conducted to see the basic academic skills possessed by children who participate in activities in Kindergarten. The method used in this research is a case study, which is a research method that uses as many data sources as possible to explain comprehensively various aspects of individuals systematically. The research subject was a 4 year old child who participated in Kindergarten activities. Research informants are mothers and teachers of the subject, as well as the tasks that have been done by the subject. Data were collected through interviews, observation and documentation. The results showed that the subject experienced obstacles in basic academic skills. It is hoped that the basic academic skills possessed by children can be honed optimally when children participate in activities in Kindergarten to face the next level of education. Research confirms that pre-school learning patterns are closely related to children's achievement later in life. Children who develop their skills more in the pre-school years perform better in primary school classes.